ADMINISTRATIVE CONTROL AS AN ALTERNATIVE PREVENTIVE MEASURE - Jilavyan, Hrant (State and Law, 2023)
Within the framework of this article, a new type of preventive measure provided for by the new Code of Criminal Procedure - Administrative control -has been discussed. Reference was made to the necessity and justification of the introduction of the mentioned preventive measure, its place in the general preventive measure system. In addition, within the framework of the article, the conditions of the application of this preventive measure, the limitations of the rights of the person envisaged as a result of its application, their nature, as well as the problems of the application of administrative control were discussed.
Keywords: administrative control; alternative preventive measure; prohibitions and restrictions; electronic monitoring